Ecology of the parasitic endohelminth community of Piaractus mesopotamicus (Holmberg, 1887) (Characiformes) from Aquidauana and Miranda Rivers, Pantanal, state of Mato Grosso do Sul, Brazil - Campos, CM.; Takemoto, RM.; Fonseca, VE.; Moraes, Flávio Ruas de [UNESP] (Instituto Internacional de Ecologia, 2009)
Neste trabalho, foram descritas a estrutura e a diversidade da comunidade endo-helmíntica de 73 exemplares de Piaractus mesopotamicus e suas interações com os hospedeiros, capturados nos rios Aquidauana e Miranda, MS. Foram encontrados 608.788 espécimes de helmintos, representados por cinco espécies: Dadaytrema oxycephala, Chabaudinema americanum, Spectatus spectatus, Rondonia rondoni e Echinorhynchus jucundum. O digenético D. oxycephala foi a espécie mais prevalente, com 91,78%, seguido do nematoda R. rondoni com 73,97%. O índice de Simpson indicou dominância entre as infracomunidades de endo-helmintos (C = 0,396), sendo D. oxycephala a espécie dominante. Dos hospedeiros amostrados, 54 continham entre duas e três espécies de endo-helmintos. Os pares R. rondoni/D. oxycephala e S. spectatus/D. oxycephala apresentaram correlações positivas significativas entre as abundâncias. Correlação positiva significativa foi observada entre comprimento total e abundância parasitária para S. spectatus (rs = - 0,2467 e p = 0,0353). A abundância de R. rondoni foi diferente estatisticamente entre o período 1/2003 e 2/2003 (p = 0,0356) e o período 1/2003 e 4/2004 (p = 0,0009). A prevalência de E. jucundum foi maior significativamente nas fêmeas.

In this study the structure and diversity of the endohelminth community, as well as its interactions with 73 specimens of Piaractus mesopotamicus are described. The fish were caught in Aquidauana and Miranda rivers, both located in the Pantantal region, in the state of Mato Grosso do Sul. A total of 608,788 specimens of helminthes were found, representing five species: Dadaytrema oxycephala, Chabaudinema americanum, Spectatus spectatus, Rondonia rondoni and Echinorhynchus jucundum. D. oxycephala was more prevalent (91.78%) followed by R. rondoni (73.97%). Simpson's index indicated dominance in the endohelminth infracommunities (C = 0.396) and D. oxycephala was considered central species. A total of 54 hosts had between 2 and 3 species of helminthes. The pairs of the species R. rondoni/D. oxycephala and S. spectatus/D. oxycephala showed significant positive correlation between abundances. There was a significant positive correlation between total length and abundance of S. spectatus (rs = -0.2467 and p = 0.0353). Abundance of R. rondoni between the periods of 1/2003 and 2/2003 (p = 0.0356) and 1/2003 and 4/2004 (p = 0.0009) was significantly different. There was significant prevalence of E. jucundum in the female hosts.
Ecologia da comunidade parasitária endo-helmíntica de Piaractus mesopotamicus (Characiformes) no rio Aquidauana, Pantanal, Mato Grosso do Sul, Brasil
Keywords: ecologia; helmintos; Pantanal; peixe; Piaractus mesopotamicus; ecology; fish; helminth; Pantanal; Piaractus mesopotamicus